Importance and correlations of characters for cowpea diversity in traditional varieties - Mendonça, Márcia; Beber, Paulo; Nascimento, Francisca Silvana; Santos, Vanderley; Marinho, José (Revista Ciência Agronômica, 2018)
Cowpea is a legume with ample plasticity, versatility and nutritional potential. It is a species widely used as a source of income and subsistence for small farmers in several Brazilian states, among them Acre. Due to the different varieties found in the State, it is the target of studies aiming at its genetic improvement. Thus, as one of the first stages of its improvement, it was aimed to determine the importance and correlations of characters for diversity and selection in traditional varieties of cowpea. The experiment was carried in completely randomized design, with plots consisting of four vase with capacity to 15.7 L, with one plant each and two replicates. The characteristics evaluated were: days for emergence, flowering (days), plant vigor (note), number of main stem nodes, apical leaflet length (mm), apical leaflet width (mm), length of pod (cm) and width of the pod (cm). The correlation coefficients (phenotypic, genotypic and environmental) were obtained, and the principal components analysis and the importance of the characters by the method proposed by Singh were carried out. The Singh method and principal components analysis were partially concordant in the distinction of the evaluated characters. The days for emergence, width of the apical leaflet, flowering and length of the apical leaflet were the main determinants for quantification of the genotypes and those that contributed the most to the variability of cowpea. The least discriminant characteristic by principal component analysis and recommended for discarding was plant vigor.